2018
DOI: 10.1080/15548627.2018.1434374
|View full text |Cite
|
Sign up to set email alerts
|

The small GTPase RAB37 functions as an organizer for autophagosome biogenesis

Abstract: Macroautophagy/autophagy is a catabolic process that is essential for cellular homeostasis. How autophagosomal vesicle forms in a spatio-temporally regulated manner remains elusive. Our recent study revealed that small GTPase, RAB37 (RAB37, member RAS oncogene family), functions as a key organizer of autophagosomal membrane biogenesis. RAB37 interacts with ATG5 (autophagy related 5) and promotes autophagosome formation by modulating ATG12-ATG5-ATG16L1 complex assembly. These findings provide new insights into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…However, whether Rho GTPases are required for FSS-induced autophagy remains unclear. A recent report indicated that the small GTPase functioned as an organizer for autophagosome biogenesis 47 . On the contrary, other studies previously reported a negative role of Rho GTPases in regulating autophagy activation 36 .…”
Section: Discussionmentioning
confidence: 99%
“…However, whether Rho GTPases are required for FSS-induced autophagy remains unclear. A recent report indicated that the small GTPase functioned as an organizer for autophagosome biogenesis 47 . On the contrary, other studies previously reported a negative role of Rho GTPases in regulating autophagy activation 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Rab GTPases regulate vesicular traffic events, including vesicle tethering, transport, and fusion. Several Rabs have been associated with the induction of autophagy (Rab18 and Rab37) [ 34 , 35 ] and regulate autophagosome biogenesis from the endoplasmic reticulum (Rab1, Rab5, and Rab32) and the Golgi apparatus (Rab33B) or facilitate the fusion of multivesicular bodies or recycling endosomes with the autophagosome (Rab11, Rab12, and Rab23) [ 36 , 37 ].…”
Section: The Rab Gtpase Network In Autophagymentioning
confidence: 99%
“…Rab18 has been characterized as a positive regulator of early autophagy in human fibroblasts and is dependent on Rab3GAP1/2, which is a RabGEF for Rab18 [ 34 ]. Activated Rab37 has been implicated in the formation of phagophores upon the induction of autophagy via interactions with the ATG5-12/16L complex to promote the elongation of isolation membranes and expression of LC3-II [ 35 ].…”
Section: The Rab Gtpase Network In Autophagymentioning
confidence: 99%
“…Rab37 has also been implicated in phagophore formation upon induction of autophagy. Specifically, in the GTP-bound state, Rab37 reportedly interacted with Atg5 and recruited Atg5-12/16L complexes to promote elongation of isolation membranes and LC3-II expression [ 66 , 67 ].…”
Section: Roles Of Rab Gtpases and Their Regulators In Autophagymentioning
confidence: 99%